Comprehensive Evaluation of the Absorption, Photophysical, Energy Transfer, Structural, and Theoretical Properties of α-Oligothiophenes with One to Seven Rings - Becker, Ralph S. (1996)
A large basis set of R-oligothiophenes with two to seven rings (R2-R7), also including thiophene, R1, have been investigated in five solvents regarding absorption, fluorescence and phosphorescence, quantum yields of fluorescence ( F) and triplet formation ( T), lifetimes of fluorescence and the triplet state, quantum yields of singlet oxygen production ( ¢), all rate constants kF, kIC, kISC, and several of the foregoing as a function of temperature. Ten different theoretical calculations across several levels including three levels of ab initio have been carried out regarding which conformer is lowest in energy and the ¢H’s among all conformers of R2, R3 and R5, as well as calculations of transitions energies of the R-oligothiophenes. We have shown that the (l) 1Bu state is the lowest singlet state for all R2-R7 in any solvent, in contradiction to previous predictions for the higher members. Based on absorption and fluorescence data and calculations of atomic charges in S0 and S1, the ground state is twisted while the excited state is planar (quinoidal-like). Significant charge transfer occurs between S0 and S1 but not S0 and T1. For all R2-R7, IC is small, k0 F is approximately constant while kISC decreases significantly from R2 to R7. The decrease is kISC is believed to arise from a decrease in matrix elements of the type á1¾CTjH¢j3¾1ñ. The essential lack of phosphorescence is assigned as originating from inter-ring twisting mode coupling between T1 and S0. Triplet energy transfer to 3O2 to produce 1O2 is highly efficient for R2-R5. Based on all data, the first Rn representative of R-polythiophene is R5.